(untitled) (Bangladesh Journal of Medical Science, 2023)
Objective: In accordance with the WHO, health is defined as integral, consisting of physical, mental, and social components that are closely interrelated and reliably correlated. Thus, the health condition of 168 university professors (39 men and 129 women) was examined. Materials and methods: They were divided by age into 3 groups (group 1 – 23-39 years old, group 2 – 40-59 years old, group 3 – 60 and above). The physiological rates were evaluated during the autumn term, and the questionnaire was conducted during the spring term (2018- 2019). Professional motivation was chosen as an indicator of the social health of a professor (the method of K. Zamfir in the modification of A. Rean). The mental health of the survey participants was assessed by the level of occupational burnout (the method of K. Maslach and S. Jackson modified by N.E. Vodopyanova). Results and Discussion: The level of physical health was determined by estimating the biological age (BA) and comparing it with the standard population rate (the express method of V.P. Voitenko). The motivation of the professors is complex and expressed in different ways. It directly depends on gender and work experience. Professors of all ages are more or less susceptible to the syndrome of occupational burnout. Conclusion: According to the BA rate, the organism of young men strongly reacts to unfavorable factors of the educational process, but it adapts with age and work experience. The organism of women has a similar dynamic, but less negative reaction. In addition, the male aging is 1.6 times more accelerated than female aging. The methodological approach used provides a big picture of the integral health of a university professor. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 432-441